Computing Dynamic Slices of Feature-Oriented Programs with Aspect-Oriented Extensions - Sahu, Madhusmita; Mohapatra, Durga Prasad (Informatica, 2020)
This paper proposes a technique to compute dynamic slices of feature-oriented programs with aspect-oriented extensions. The technique uses a dependence based intermediate program representation called composite feature-aspect dependence graph (CFADG) to represent feature-oriented software that contain aspects. The CFADG of a feature-oriented program is based on the selected features that are composed to form a software product and the selected aspects to be weaved. The proposed dynamic slicing technique has been named feature-aspect node marking dynamic slicing (FANMDS) algorithm. The proposed feature-aspect node marking dynamic slicing algorithm is based on marking and unmarking the executed nodes in the CFADG suitably during run-time. The advantage of the proposed approach is that no trace le is used to store the execution history. Also, the approach does not create any additional nodes during run-time.